Total Lactic Acid Bacteria and pH Values in Lu'at Fermentation with Different Salt Levels and Fermentation Duration - Joanivita Paulo Gulo Soru; Paulus Risan Funan Lalong; Maria Novalina Naben (International Journal Labs, 2025)
Cayenne pepper (Capsicum frutescens L.) is an important commodity in Indonesian cuisine for cooking spices and chilli sauce. Sambal is in demand as a condiment with a spicy taste. Lu'at is a typical chilli sauce from Timor, East Nusa Tenggara which is used as a condiment with a spicy taste, which is prepared by traditionally fermenting chillies, lime, salt, and other additional ingredients. One type of fermentation is fermentation with lactic acid bacteria (LAB). This research aims to determine the total number of lactic acid bacteria and the pH value of lu'at fermented with different salt levels and fermentation times. This research used two factorial Completely Randomized Design (CRD), namely salt content (G) (0%, 5% and 10%) and fermentation time (F) (0, 7 and 14 days) with 3 repetitions. The data obtained was analyzed using Analysis of Variance (ANOVA) and if there were significant differences then it was continued with the Turkey Test. Lu'at is made from a mixture of crushed cayenne pepper, lime slices (Citrus aurantifolia), and basil leaves (Ocimum basilicum) in a ratio of 150:10:5. The results showed that there was a significant difference in the average total lactic acid bacteria between treatments with 5% and 10% salt content (P>0.05). In contrast, there was no significant difference (P<0.05) in the treatment with fermentation time and the interaction between salt content and storage time. The average total lactic acid bacteria were significantly different in the 5% and 10% salt content treatments (p>0.05). At the same time, there was no significant difference (p<0.05) based on fermentation time and the interaction between salt content and storage time. The highest total of lactic acid bacteria was in the treatment with a salt content of 5% and a fermentation time of 7 days (4.3 x 107 CFU/g). The pH value in lu'at fermentation was not significantly different in all treatments (p<0.05) with an average pH value range of 3.57 – 3.98.